Neither a toda virolla nor tumbados a la bartola. A corpus analysis of phraseologically bound spanish words - Cecilia López Roig (Revista de Lingüística y Lenguas Aplicadas)
This article presents results on the Spanish phraseologically bound words (PLF), also known as cranberry words, based on a corpus analysis. If up to now the different Spanish PLF had been collected introspectively, this article presents a list of the Spanish PLF indicating the phraseological fixation index (IFF) of each one of them in the phraseological unit (UF) that contains them and ordered by the weighted phraseological fixation index (IFFP). To do this, it has been necessary to obtain from the corpus the total number of occurrences of the PLF (NPLF) and to analyse the fixation of these elements both inside the UF or the UFS that contain them (FFPLF) and outside the UF, in their free use. Furthermore, the quantitative data of the PLF which was collected in four differentiated groups from two matrices (the FFPLF matrix and the NPLF matrix) present interesting results on this type of elements.